2011
DOI: 10.2500/ajra.2011.25.3540
|View full text |Cite
|
Sign up to set email alerts
|

Use of Montelukast Alone or in Combination with Desloratadine or Levocetirizine in Patients with Persistent Allergic Rhinitis

Abstract: Montelukast alone or in combination with antihistamines gave a gradual increase in nasal symptom improvement within 6 weeks of treatment in patients with persistent AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 22 publications
1
36
0
3
Order By: Relevance
“…Although a daily dose of 10 mg of montelukast provides a consistent benefit over long periods, the therapeutic gains are lost shortly after discontinuation, as suggested by studies of its use on other disease states. [33][34][35][36] Allergic rhinitis and asthma, diseases that are known to be improved by LTAs, [8][9][10] often coexist with CRSwNP, and thus must be considered when assessing the efficacy of treatment. In most trials not specifically addressing the effects of LTAs on atopy or asthma these conditions were randomized between the treatment groups or sufficiently addressed as a patient subset so as to balance the effects of these conditions on patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a daily dose of 10 mg of montelukast provides a consistent benefit over long periods, the therapeutic gains are lost shortly after discontinuation, as suggested by studies of its use on other disease states. [33][34][35][36] Allergic rhinitis and asthma, diseases that are known to be improved by LTAs, [8][9][10] often coexist with CRSwNP, and thus must be considered when assessing the efficacy of treatment. In most trials not specifically addressing the effects of LTAs on atopy or asthma these conditions were randomized between the treatment groups or sufficiently addressed as a patient subset so as to balance the effects of these conditions on patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…7 This process can be inhibited either by blocking the receptor with an LT receptor antagonist, such as montelukast, or by preventing the formation of cysteinyl-LTs with a 5-lipooxygenase inhibitor, such as zileuton. LT antagonists (LTAs) have proven efficacious in chronic inflammatory conditions of the airways, including allergic rhinitis, asthma, and aspirinexacerbated respiratory disease (AERD), [8][9][10][11] all diseases that often coexist with CRSwNP. Several studies have shown positive effects of LTAs as a primary treatment for CRSwNP.…”
mentioning
confidence: 99%
“…To contradict this finding, many comparative studies in AR patients have concluded that individual antihistamines such as fexofenadine, loratadine, [12] and desloratidine [7,13] are as effective as their combinations with montelukast, thus not justifying the various fixed-dose combinations (FDC) of antihistamines with montelukast available in market. Literature survey also revealed that comparative studies of other antihistamines in AR such as ebastine, a secondgeneration drug, with its combination with montelukast are very much scanty.…”
Section: Introductionmentioning
confidence: 91%
“…In these [12,13] studies, along with subjective symptoms, objective evidence of anti-allergy such as domiciliary nasal peak flow, nasal eosinophilia, and serum soluble intracellular adhesion molecule were also measured, and individual antihistamines had upper hand over their combinations with montelukast. In contrast, other contradictory studies have shown that the combination of different antihistamines with montelukast had controlled not only subjective symptom scores [18,19] but also produced significant objective proof of anti-allergic actions, more than individual antihistamines, in AR.…”
Section: Discussionmentioning
confidence: 99%
“…Although second-generation antihistamines cause barely any drowsiness, there have been some reports regarding cardiac side effects, such as QT prolongation, which may lead to serious cardiac arrhythmia (Higaki et al, 2012). Fortunately, this vital cardiac side effect has rarely been observed in clinical practice; however, when prescribing AR therapies, clinicians should pay special attention to other comorbid diseases of AR patients, such as organic heart disease, cardiac arrhythmia, and electrolyte imbalance (Adsule and Misra, 2010;Ciebiada et al, 2011;Cox et al, 2012).…”
Section: Discussionmentioning
confidence: 99%